Toxicological impact of microplastics and nanoplastics on humans: understanding the mechanistic aspect of the interaction - Alqahtani, Saeed; Alqahtani, Shaherah; Saquib, Quaiser; Mohiddin, Fayaz (Frontiers in Toxicology, 2023)
Plastic is a pervasive material that has become an indispensable part of our daily lives and is used in various commercial products. However, plastic waste has significantly impacted the environment, accumulating in water and land ecosystems and harming all forms of life. When plastic degrades, it breaks down into smaller particles called microplastics (MPs), which can further breakdown into nanoplastics (NPs). Due to their small size and potential toxicity to humans, NPs are of particular concern. During the COVID-19 pandemic, the production of plastic had reached unprecedented levels, including essential medical kits, food bags, and personal protective equipment (PPE), which generate MPs and NPs when burned. MPs and NPs have been detected in various locations, such as air, food, and soil, but our understanding of their potential adverse health effects is limited. This review aims to provide a comprehensive overview of the sources, interactions, ecotoxicity, routes of exposure, toxicity mechanisms, detection methods, and future directions for the safety evaluation of MPs and NPs. This would improve our understanding of the impact of MPs and NPs on our health and environment and identify ways to address this global crisis.